Lithium ion battery

By using O2 phase lithium cobalt oxide and fluorine-containing compounds in lithium-ion batteries, the interactions in the battery are controlled, and the cycle stability, charge and discharge efficiency and safety of lithium batteries are solved, and higher battery performance is achieved.

CN119601746APending Publication Date: 2025-03-11ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717680.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

How to improve the cycle stability, charge and discharge efficiency and safety of O2-phase lithium cobalt oxide lithium batteries is affected by structural instability and interface side reactions.

Method used

By using lithium cobalt oxide of O2 phase as the positive electrode active material in lithium-ion batteries and adding fluorine-containing compounds to the electrolyte, the mass content of the fluorine-containing compounds and the half-maximum width of the X-ray diffraction pattern of the positive electrode active material can be controlled, and a specific relationship (90≤F/Z≤375) is met to synergistically improve battery performance.

Benefits of technology

It effectively improves the circulation stability, charging and discharging efficiency and safety of lithium-ion batteries, and reduces internal stress and heat changes of the battery by forming a stable interface mask and inhibiting side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601746A_ABST
    Figure CN119601746A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery. The lithium ion battery comprises a positive plate, a negative plate, electrolyte and a diaphragm, wherein the positive plate comprises a positive current collector and a positive active material layer arranged on at least one side surface of the positive current collector, and the positive active material layer comprises a positive active material; the positive electrode active material comprises O2-phase lithium cobalt oxide, an X-ray diffraction pattern of the positive electrode active material has a (103) peak corresponding to a 103 crystal face, and the half-peak width of the (103) peak is Z; the electrolyte comprises a fluorine-containing compound, and based on the total mass of the electrolyte, the mass content of the fluorine-containing compound is F; wherein F and Z satisfy 90 < = F / Z < = 375. The lithium ion battery has relatively high cycling stability, charging and discharging efficiency and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a lithium ion battery. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in various smart electronic products, power equipment, and energy storage systems due to their advantages such as low self-discharge rate, environmental protection, light weight, and wide operating temperature range. However, with the growing demand for energy storage by consumers, there is an urgent need to further develop new materials or technologies to improve the energy density of lithium-ion batteries. As one of the important components of lithium-ion batteries, positive electrode active materials play a key role in improving their energy density. Among the many positive electrode materials, lithium cobalt oxide is the main positive electrode material for 3C consumer electronic lithium batteries due to its advantages such as high specific capacity, high discharge platform, and compaction density.

[0003] There are three different structures of lithium cobalt oxide, namely O1 structure, O2 structure and O3 structure. Among them, the structural stability of O1 structure is extremely poor, while the structures of O2 and O3 are relatively stable. O2 has a higher energy density than O3, but the oxygen atoms in the O2 phase of lithium cobalt oxide are stacked in an ABCBAB manner. This arrangement increases the resistance of lithium ions to escape and embed between layers, affecting the electrochemical cycle performance and stability of the material. Moreover, lithium cobalt oxide with this structure is in a metastable state. During the charge and discharge process, phase changes are prone to occur, accompanied by serious interfacial side reactions, cobalt metal dissolution and oxygen evolution, resulting in decreased battery cycle stability, low charge and discharge efficiency and safety risks.

[0004] Therefore, how to improve the cycle stability, charge and discharge efficiency, and safety of lithium batteries including O2-phase lithium cobalt oxide is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of the above-mentioned defects, the present invention provides a lithium-ion battery, wherein the positive electrode active material includes O2-phase lithium cobalt oxide, and the electrolyte includes a fluorine-containing compound. By making the fluorine-containing compound and the O2-phase lithium cobalt oxide satisfy a specific relationship, the cycle stability, charge and discharge efficiency and safety of the battery are effectively improved.

[0006] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material;

[0007] The positive electrode active material comprises lithium cobalt oxide in an O2 phase, and the X-ray diffraction spectrum of the positive electrode active material has a (103) peak corresponding to a 103 crystal plane, and the half-peak width of the (103) peak is Z, in units of degrees;

[0008] The electrolyte includes a fluorine-containing compound, and based on the total mass of the electrolyte, the mass content of the fluorine-containing compound is F, in units of %;

[0009] Among them, F and Z satisfy 90≤F / Z≤375.

[0010] Furthermore, the O2 phase lithium cobalt oxide includes Li x Na y Co z M n O2, wherein 0.8<x<1.3, 0<y<0.04, 0.001<n<0.02, 0.98<z<0.999, and M is at least one of Al, Mg, Ti, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te;

[0011] And / or, the fluorine-containing compound includes at least one of fluoroethylene carbonate, trifluoroethyl methyl carbonate, difluoroacetamide, fluorocarbamate, fluorotetramethylene sulfone, fluorotriethyl phosphate, 2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 2,2-difluoroethyl acetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorobenzene, fluoroacetonitrile, and fluoroadiponitrile.

[0012] Further, 10%≤F≤45%, and / or, 0.1°≤Z≤0.2°.

[0013] Furthermore, the positive electrode active material also includes lithium cobalt oxide in the O3 phase;

[0014] Preferably, the chemical composition of the lithium cobalt oxide in the O3 phase is Li a Co e N f O2, wherein 0.9<a<1.1, 0.95≤e≤1, 0≤f≤0.05, and N includes at least one of Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te.

[0015] Further, based on the total mass of the positive electrode active material, the mass proportion C of the lithium cobalt oxide in the O2 phase satisfies: 5%≤C≤60%; preferably, 5%≤C≤60%;

[0016] And / or, the electrolyte further includes a nitrile additive; preferably, the nitrile additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, trans-butene dinitrile, trans-hexene dinitrile, acrylonitrile, cinnamonitrile, cyclohex-1-enyl acetonitrile, 3,3-dimethylacrylonitrile, pentenenitrile, 1,4-dicyano-2-butene, and isophthalonitrile; more preferably, based on the total mass of the electrolyte, the mass content N of the nitrile additive satisfies: 2%≤N≤7%.

[0017] Furthermore, N, F and C satisfy 0.5≤(N+F) / C≤10.

[0018] Furthermore, the mass content of the Na element in the positive electrode active material layer is 100 to 5000 ppm;

[0019] And / or, the mass content of Co element in the negative electrode sheet is 2 to 50 ppm;

[0020] And / or, after the lithium ion battery is formed, the mass content of Co element in the electrolyte is 5 to 25 ppm.

[0021] Furthermore, the electrolyte also includes 1,3-propane sultone and / or 1,3-propylene sultone;

[0022] Preferably, based on the total mass of the electrolyte, the mass content of the 1,3-propane sultone is 1 to 5%;

[0023] Preferably, based on the total mass of the electrolyte, the mass content of 1,3-propene sultone is 0.3-3%.

[0024] Furthermore, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; the single-side thickness of the negative electrode active material layer is 35 to 72 μm;

[0025] Preferably, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material;

[0026] More preferably, based on the total mass of the negative electrode active material layer, the mass content of the silicon-carbon material is 3% to 25%.

[0027] Furthermore, the positive electrode current collector and / or the negative electrode current collector comprises a first metal conductive layer, an organic polymer material layer and a second metal conductive layer which are stacked.

[0028] The implementation of the present invention has at least the following advantages:

[0029] The present invention makes the electrolyte in the lithium ion battery include a fluorine-containing compound and uses a special positive electrode active material (including lithium cobalt oxide in the O2 phase). The positive electrode active material has a (103) peak corresponding to the 103 crystal plane in the X-ray diffraction spectrum, and controls the mass content F of the fluorine-containing compound in the electrolyte and the half-peak width of the (103) peak to Z, so that F and Z satisfy a specific relationship, that is, 90≤F / Z≤375, thereby making the electrolyte and the positive electrode active material cooperate with each other, effectively improving the cycle stability, charge and discharge efficiency and safety of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the X-ray diffraction pattern of the positive electrode active material in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material;

[0033] The positive electrode active material includes lithium cobalt oxide in an O2 phase, and the X-ray diffraction spectrum of the positive electrode active material has a (103) peak corresponding to a 103 crystal plane, and the half-peak width of the (103) peak is Z, and the unit is °;

[0034] The electrolyte includes a fluorine-containing compound, and the mass content of the fluorine-containing compound based on the total mass of the electrolyte is F, in units of %;

[0035] Among them, F and Z satisfy 90≤F / Z≤375.

[0036] In detail, when F is 20% and Z is 0.1°, F / Z=200. Exemplarily, F / Z is 90, 120, 150, 180, 210, 240, 270, 300, 330, 360 or 375.

[0037] The present invention includes a fluorine-containing compound in the electrolyte, and the positive electrode active material includes an O2-phase lithium cobalt layered oxide, and the positive electrode active material has a (103) peak corresponding to the 103 crystal plane in the X-ray diffraction spectrum, and the mass content of the fluorine-containing compound in the electrolyte is controlled to be F and the half-peak width Z of the (103) peak satisfies 90≤F / Z≤375, which can effectively improve the cycle stability, charge and discharge efficiency and safety of lithium-ion batteries. Based on this phenomenon, the inventors analyzed and believed that the reason may be:

[0038] The half-width of the positive electrode active material means the distortion or defect of the positive electrode material lattice. The O2 phase lithium cobalt oxide of the present application can achieve its structural stability within a specific range. If the half-width of the O2 phase lithium cobalt oxide is too large, it indicates that the atomic arrangement in the crystal is more disordered, and there are more distortions or defects in the positive electrode material, which aggravates the side reaction with the electrolyte and causes the structural instability of the positive electrode material, affecting its cycle stability. If the half-width is too small, it indicates that the atomic arrangement in the crystal is more ordered and there are few defects, which makes it more difficult for ions to embed and remove, shortening the cycle life of the battery. At the same time, it will also cause the internal pressure of the battery to increase during charging and discharging, generate excessive heat, and affect the safety of the battery.

[0039] By adding fluorine-containing compounds to the electrolyte and controlling the half-peak width Z of the positive electrode active material and the mass content F of the fluorine-containing compounds in the electrolyte to satisfy 90≤F / Z≤375, the two can work well together. The fluorine-containing compounds in the electrolyte can interact well with the defects in the positive electrode active material, participate in the interfacial reaction during the charge and discharge process, and form a stable and firm fluorine-containing interface film (CEI film) on the surface of the positive electrode active material, thereby improving the interfacial stability of the positive electrode active material, and thus making the battery have a higher cycle stability. Moreover, when the battery falls, the interface film on the surface of the positive electrode active material may rupture due to physical impact, resulting in the fresh active material surface being exposed in the electrolyte, and the fluorine-containing compounds can quickly form an interface film on the new surface, effectively avoiding the occurrence of internal short circuits, reducing local heat generation, and improving the safety performance of the battery.

[0040] At the same time, by making the positive electrode active material include O2-phase lithium cobalt oxide, the crystal plane orientation of the material is uniform, which can effectively improve the charge and discharge efficiency of the battery, but at the same time, the mechanical strength of the material is low, and it is easy to break during the cycle charge and discharge process, resulting in performance degradation. The fluorine-containing compound in the electrolyte helps to form a fluorine-containing interface film, which effectively inhibits the side reaction between the electrolyte and the O2-phase lithium cobalt oxide in the positive electrode active material, and the problem of Co ion dissolution in the O2-phase lithium cobalt oxide, which can not only reduce gas production, but also improve the structural stability of the O2-phase lithium cobalt oxide. In addition, the fluorine atoms in the fluorine-containing compound can complex with the oxygen atoms on the surface of the O2-phase lithium cobalt oxide, inhibiting the escape of lattice oxygen, thereby further improving the structural stability of the O2-phase lithium cobalt oxide; and the improvement of structural stability can also reduce the internal stress and heat changes of the battery caused by phase change and structural collapse, and improve the hot box performance of the battery.

[0041] When F / Z is lower than 90, the content of fluorine-containing compounds in the electrolyte is too small to cooperate with the defects in the positive electrode active material to form a stable interface film, resulting in increased side reactions, more Co ion dissolution, poor material structure stability and other problems, reducing the battery's cycle performance; at the same time, when the battery is subjected to physical impact, there is not enough fluorine-containing compounds to act on the newly exposed active material surface to form an interface film, resulting in a decrease in battery safety performance. When F / Z is higher than 375, the content of fluorine-containing compounds in the electrolyte is too high, and the viscosity of the electrolyte increases, which not only leads to increased impedance and hinders ion transmission, but also causes more heat to be generated during charging and discharging, decomposition of substances in the electrolyte, aggravated gas production, shortened battery cycle life, and reduced battery safety life.

[0042] Therefore, when the above relationship is satisfied between the fluorine-containing compounds and the positive electrode active materials in lithium-ion batteries, the two work together to comprehensively improve the battery's cycle stability, charge and discharge efficiency, and safety.

[0043] In addition, fluorine-containing compounds are non-flammable and have a high boiling point, which can further ensure the safety of lithium-ion batteries.

[0044] The (103) peak in the present invention refers to a diffraction peak located between 46.5° and 47.6°.

[0045] The "fluorine-containing compound" in the present invention refers to an organic compound containing fluorine element.

[0046] The present invention does not specifically limit the composition of the positive electrode current collector, which can be selected from positive electrode current collectors commonly used in the art, such as any one of aluminum foil, nickel foil, and composite current collectors.

[0047] The present invention does not specifically limit the type of the fluorine-containing compound, as long as it contains fluorine element.

[0048] The present invention does not specifically limit the chemical composition of the O2 phase lithium cobalt oxide. It only needs to include a (103) peak corresponding to the 103 crystal plane in the X-ray diffraction spectrum of the positive electrode active material of the O2 phase lithium cobalt oxide, and the half-peak width Z of the (103) peak and the mass content F of the fluorine-containing compound in the electrolyte satisfy 90≤F / Z≤375.

[0049] The present invention does not specifically limit the sources of the fluorine-containing compound and the O2-phase lithium cobalt oxide, and any commercially available product or product prepared by a conventional preparation method known to those skilled in the art may be used.

[0050] In one embodiment, the chemical composition of the lithium cobalt oxide in the O2 phase is Li x Na y Co z M n O2, wherein 0.8<x<1.3, 0<y<0.04, 0.001<n<0.02, 0.98<z<0.999, and M is at least one of Al, Mg, Ti, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te.

[0051] On the one hand, Na doping can change the electronic structure of O2-phase lithium cobalt oxide and improve its conductivity, thereby effectively reducing the internal resistance of the battery; and Na sites can also induce the reduction of fluorine-containing compounds on the surface of O2-phase lithium cobalt oxide to generate CEI containing LiF, effectively improving the toughness of the interface film. On the other hand, after Li is released, the positive electrode crystal structure loses its supporting sites, resulting in the contraction of the crystal structure and the reduction of the interlayer distance, causing irreversible capacity loss. M doping can form stronger MO bonds, maintain the stability of lattice oxygen, provide stable sites, improve the stability of the layered structure, inhibit the contraction of the crystal structure and the reduction of the interlayer distance, and effectively increase the working voltage of O2-phase lithium cobalt oxide, so that it can work stably in a higher voltage range, so that the battery has higher energy density and cycle performance. On the other hand, the improvement of the structural stability of O2-phase lithium cobalt oxide can prevent the half-peak width of the positive electrode active material from changing drastically during the cycle, resulting in the structural collapse of the positive electrode material, and further improve the cycle performance of the material.

[0052] The chemical composition of the present invention is Li x Na y Co z M n O2-phase lithium cobalt oxide has a layered crystal structure of α-sodium ferrite type and belongs to the R3m space group. In its crystal structure, oxygen ions (O 2 -) are hexagonally packed, and lithium ions (Li + ) and cobalt ions (Co3+ ) are each located in alternating octahedral positions in the cubic close-packed framework of oxygen ions.

[0053] In a specific embodiment, the fluorine-containing compound includes at least one of fluoroethylene carbonate, trifluoroethyl methyl carbonate, difluoroacetamide, fluorocarbamate, triethyl fluorophosphate, 2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 2,2-difluoroethyl acetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorobenzene, fluoroacetonitrile, and fluoroadiponitrile.

[0054] When the fluorine-containing compound includes at least one of the aforementioned compounds, the fluorine-containing compound can better cooperate and coordinate with the O2 phase lithium cobalt oxide, further improving the cycle stability, charge and discharge efficiency and safety of the battery.

[0055] When the fluorine-containing compound is a plurality of specific compounds among the aforementioned compounds, the present invention does not specifically limit the ratio between the plurality of specific compounds.

[0056] In a specific embodiment, 10%≤F≤45%. Within this range, it is possible to ensure that the electrolyte contains sufficient fluorine-containing compounds to participate in the formation of the interface film and complex with oxygen atoms on the surface of the O2 phase lithium cobalt oxide, thereby improving the structural stability of the material and reducing heat generation, thereby improving the cycle performance and safety performance of the battery; at the same time, it is possible to avoid the increase in electrolyte viscosity caused by excessive fluorine-containing compounds, thereby ensuring that the electrolyte has a high conductivity, thereby improving the rate performance of the battery.

[0057] Illustratively, F is 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%.

[0058] In a specific embodiment, 0.1°≤Z≤0.2°. Within this range, there are fewer defects in the grains and the crystal planes are uniformly oriented, which is beneficial to reduce the occurrence of side reactions and make the battery have higher cycle stability; at the same time, it can also reduce the insertion resistance of lithium ions and further improve the charge and discharge efficiency of the material.

[0059] Illustratively, Z is 0.1°, 0.12°, 0.14°, 0.16°, 0.18° or 0.2°.

[0060] In a specific embodiment, the positive electrode active material further comprises lithium cobalt oxide in the O3 phase;

[0061] Preferably, the chemical composition of the lithium cobalt oxide in the O3 phase is Li a Co e N fO2, wherein 0.9<a<1.1, 0.95≤e≤1, 0≤f≤0.05, and N includes at least one of Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te. By using surface coating (e.g., high-speed solid-phase coating method) and doping (high-temperature solid-phase synthesis method) and other technologies to make the positive electrode active material simultaneously include lithium cobalt oxide in O2 phase and O3 phase, the structural stability of the positive electrode active material can be effectively improved when the battery is overcharged and the voltage is increased, thereby improving the anti-overcharge performance of the battery.

[0062] In a specific embodiment, based on the total mass of the positive electrode active material, the mass proportion C of the lithium cobalt oxide in the O2 phase satisfies: 5%≤C≤60%; preferably, 5%≤C≤60%. Within this range, the cycle stability of the battery can be further improved and a higher energy density can be ensured.

[0063] Illustratively, C is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0064] In a specific embodiment, the electrolyte further includes a nitrile additive; preferably, the nitrile additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, trans-butene dinitrile, trans-hexene dinitrile, acrylonitrile, cinnamonitrile, cyclohex-1-enyl acetonitrile, 3,3-dimethylacrylonitrile, pentenenitrile, 1,4-dicyano-2-butene, and isophthalonitrile; more preferably, based on the total mass of the electrolyte, the mass content N of the nitrile additive satisfies: 2%≤N≤7%.

[0065] When the electrolyte also includes nitrile additives, the lone pair of electrons on the nitrogen atom in the nitrile additive can produce a complex reaction with the cobalt ion, further preventing the Co ions in the O2 phase lithium cobalt oxide from dissolving into the electrolyte and migrating to the negative electrode, thereby further improving the cycle stability of the battery; however, the reducibility of nitrile additives is poor, and they are easily decomposed at low voltages and corrode the current collector; while the fluorine-containing compounds in the electrolyte can form a fluorine-containing interface film (SEI film) on the surface of the negative electrode active material, and improve the stability of the SEI film through the hydrogen bonding of fluorine atoms and hydrogen atoms, effectively inhibiting the corrosion of the nitrile additive to the negative electrode.

[0066] Furthermore, when the nitrile additive includes at least one of the aforementioned specific compounds, the complexation between the nitrile additive and the cobalt ions can be further enhanced, thereby making the battery have better cycle performance.

[0067] Furthermore, when the mass content N of the nitrile additive in the electrolyte is within the aforementioned range, it can not only ensure that the nitrile additive can be well complexed with the cobalt ions to inhibit the dissolution of cobalt ions; it can also better cooperate with the fluorine-containing compounds to avoid excessive content of the nitrile additive and weakening the effect of the fluorine-containing compounds, thereby effectively reducing the corrosion of the nitrile additive to the negative electrode and improving the cycle stability of the battery.

[0068] Illustratively, N is 2%, 3%, 4%, 5%, 6% or 7%.

[0069] The present invention does not specifically limit the source of the nitrile additive, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0070] When the nitrile additive is a plurality of specific compounds among the aforementioned compounds, the present invention does not specifically limit the ratio between the plurality of specific compounds.

[0071] In a specific embodiment, N, F and C satisfy 0.5≤(N+F) / C≤10. Within this range, on the one hand, the nitrile compound can be well complexed with the Co ions in the O2 phase lithium cobalt oxide, reducing the dissolution of Co ions in the material; on the other hand, the electrolyte contains enough fluorine-containing compounds to participate in the formation of the interface film on the surface of the negative electrode, effectively avoiding the corrosion of the nitrile compound on the negative electrode current collector; thereby comprehensively improving the cycle stability of the battery under the high voltage system.

[0072] When (N+F) / C is lower than 0.5, the complexation effect of nitrile compounds on Co ions is reduced, and there are not enough fluorine-containing compounds to participate in the formation of the interface film, which will not only cause Co ions to dissolve to a certain extent, but also cause nitrile compounds to corrode the negative electrode collector, thereby reducing the battery cycle performance.

[0073] When (N+F) / C is higher than 10, excessive nitrile compounds and fluorine-containing compounds will cause the electrolyte to decompose, aggravate gas production, generate more heat, and affect the cycle life and safety performance of the battery; at the same time, it will also cause the electrolyte viscosity to be too high, affecting the electrolyte conductivity and ion transfer efficiency, thereby affecting the battery's rate performance.

[0074] Illustratively, (N+F) / C is 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0075] In a specific embodiment, the mass content of the Na element in the positive electrode active material layer is 100 to 5000 ppm. Within this range, the crystal structure can be further stabilized, the structural collapse caused by phase change can be reduced, and the cycle life of the battery under high voltage can be improved; at the same time, the migration of lithium ions will not be hindered due to excessive Na content, so that the battery has a higher charge and discharge efficiency. In addition, the Na can further induce the reduction of fluorine-containing compounds, so that the interface film has better toughness, thereby better alleviating the stress caused by the volume expansion of the positive electrode material, preventing the CEI film from rupturing, and improving the cycle performance of the battery.

[0076] Exemplarily, the mass content of the Na element in the positive electrode sheet is 100 ppm, 800 ppm, 1500 ppm, 2200 ppm, 2900 ppm, 3600 ppm, 4300 ppm or 5000 ppm.

[0077] The mass content of the Na element in the positive electrode sheet of the present invention can be obtained by inductively coupled plasma mass spectrometry (ICP) testing.

[0078] In a specific embodiment, the mass content of the Co element in the negative electrode sheet is 2 to 50 ppm. The Co element in the negative electrode sheet comes from the dissolution of Co in the positive electrode active material. Although the dissolution of Co will reduce the structural stability of the positive electrode active material, the dissolution to a certain extent helps to form a dense CoO layer on the surface of the negative electrode, which is beneficial to improve the cycle stability of the battery. However, excessive dissolution of Co will not only lead to a sharp decline in the structural stability of the positive electrode active material, but also cause the CoO layer on the surface of the negative electrode to be too thick, increase the transmission path of lithium ions, and increase the battery impedance. , Reduced performance. Therefore, by further controlling the F / Z value, the content of the Co element in the negative electrode sheet is within the aforementioned range, which helps to improve the cycle stability of the battery.

[0079] Illustratively, the mass content of the Co element in the negative electrode sheet is 2 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm or 50 ppm.

[0080] It should be noted that the Co element in the negative electrode sheet may come from the Co dissolved from the positive electrode to the negative electrode after the lithium-ion battery is formed.

[0081] Specifically, the formation mechanism in the present invention is: charging at 80° C. at 0.2C to an upper limit voltage of 4.45V.

[0082] The mass content of the Co element in the negative electrode sheet of the present invention can be obtained by inductively coupled plasma mass spectrometry (ICP) testing.

[0083] In a specific embodiment, after the lithium-ion battery is formed, the mass content of the Co element in the electrolyte is 5 to 25 ppm. Within this range, the conductivity of the electrolyte can be effectively improved, thereby improving the charge and discharge efficiency of the battery.

[0084] Exemplarily, the mass content of the Co element in the electrolyte is 5 ppm, 10 ppm, 15 ppm, 20 ppm or 25 ppm.

[0085] The mass content of the Co element in the electrolyte of the present invention can be obtained by inductively coupled plasma mass spectrometry (ICP) testing.

[0086] In a specific embodiment, the electrolyte further includes 1,3-propane sultone and / or 1,3-propylene sultone;

[0087] Preferably, based on the total mass of the electrolyte, the mass content of 1,3-propane sultone is 1 to 5%;

[0088] Preferably, based on the total mass of the electrolyte, the mass content of 1,3-propene sultone is 0.3-3%.

[0089] When the electrolyte also includes at least one of 1,3-propane sultone and 1,3-propylene sultone, it can cooperate with the fluorine-containing compound to form an SEI film with an inner layer containing fluorine and an outer layer containing sulfur on the surface of the negative electrode, so that the SEI film not only has high stability, but also has good elasticity, thereby improving the stability of the negative electrode.

[0090] Furthermore, when the mass content of 1,3-propane sultone or 1,3-propylene sultone in the electrolyte is within the aforementioned range, not only can the stability and elasticity of the SEI film be further improved, but also the transmission of lithium ions will not be hindered, so that the battery has better cycle stability and charge and discharge efficiency.

[0091] Illustratively, the mass content of 1,3-propane sultone in the electrolyte is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0092] Illustratively, the mass content of 1,3-propene sultone in the electrolyte is 0.3%, 0.6%, 0.9%, 1.2%, 1.5%, 1.8%, 2.1%, 2.4%, 2.7% or 3%.

[0093] The present invention does not specifically limit the source of 1,3-propane sultone, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0094] In a specific embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; the single-side thickness of the negative electrode active material layer is 35 to 72 μm;

[0095] Preferably, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material;

[0096] More preferably, the mass content of the silicon-carbon material is 3% to 25% based on the total mass of the negative electrode active material layer.

[0097] By making the thickness of the negative electrode active material layer in the negative electrode sheet within the aforementioned range, on the one hand, it can not only ensure that the negative electrode sheet contains sufficient negative electrode active material, thereby increasing the effective capacity of the battery; but also can avoid the problem of a large number of decomposition products of fluorine-containing compounds, thereby reducing the battery charging and discharging efficiency; on the other hand, it can avoid the poor wettability of the electrolyte caused by the excessive thickness of the negative electrode active material layer, thereby ensuring better wettability between the fluorine-containing compound and the electrode sheet, thereby effectively reducing the internal resistance of the battery and increasing the charging speed of the battery.

[0098] Furthermore, the negative electrode active material includes silicon-carbon material, which can further improve the energy density of the battery. However, the silicon-carbon material has a large volume change during the cycle process; while the fluorine-containing substances in the electrolyte help to form a strong SEI film on the negative electrode surface, which plays a role in volume change, thereby effectively improving the structural stability of silicon-carbon and increasing battery life.

[0099] Furthermore, based on the total mass of the negative electrode active material layer, the mass content of the silicon-carbon material is 3% to 25%. Within this range, not only can the battery have a higher energy density, but also the high cycle stability of the battery can be ensured.

[0100] Illustratively, the mass content of the silicon carbon material is 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23% or 25% based on the total mass of the negative electrode active material layer.

[0101] Furthermore, the negative electrode active material may also include at least one of graphite, silicon oxide, silicon carbide, hard carbon, and soft carbon.

[0102] Furthermore, the negative electrode active material layer also includes a binder and a conductive agent.

[0103] The present invention does not specifically limit the specific types of the binder and the conductive agent, which can be selected conventionally in the art. For example, the binder includes at least one of polyvinyl alcohol, polytetrafluoroethylene, polyolefin, polyvinylidene fluoride, styrene-butadiene rubber, and fluorinated rubber; the conductive agent includes at least one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, and graphene.

[0104] In a specific embodiment, the positive electrode current collector and / or the negative electrode current collector includes a first metal conductive layer, an organic polymer material layer, and a second metal conductive layer which are stacked.

[0105] In detail, in one embodiment, the positive electrode current collector includes a first metal conductive layer, an organic polymer material layer, and a second metal conductive layer that are stacked; in another embodiment, the negative electrode current collector includes a first metal conductive layer, an organic polymer material layer, and a second metal conductive layer that are stacked; in yet another embodiment, the positive electrode current collector and the negative electrode current collector include a first metal conductive layer, an organic polymer material layer, and a second metal conductive layer that are stacked.

[0106] When the positive electrode current collector and the negative electrode current collector have the aforementioned structure, not only can the weight of the battery be reduced, but also the mechanical tensile strength of the current collector can be improved, which can effectively reduce the probability of short circuit during mechanical abuse and improve the safety of the battery; and to a certain extent, it can also improve the cycle performance and charge and discharge efficiency of the battery.

[0107] Specifically, the upper and lower surfaces of the organic polymer material layer are respectively provided with a first metal conductive layer and a second metal conductive layer.

[0108] It can be understood that the upper and lower surfaces of the organic polymer material layer refer to the outermost surfaces in the length direction and width direction of the organic polymer material layer, that is, the largest and opposite front and back surfaces among the six surfaces of the organic polymer material layer.

[0109] Preferably, the first metal conductive layer and the second metal conductive layer in the positive electrode current collector independently include at least one of aluminum, nickel, titanium, and stainless steel; further, it can also be a composite material of the aforementioned substances (at least two of aluminum, nickel, titanium, and stainless steel).

[0110] Preferably, the first metal conductive layer and the second metal conductive layer in the negative electrode current collector independently include at least one of copper, nickel, stainless steel, and carbon materials; further, it can also be a composite material of the aforementioned substances (at least two of copper, nickel, stainless steel, and carbon materials).

[0111] Preferably, the organic polymer material layer in the positive electrode current collector and / or the negative electrode current collector includes at least one of polyimide (PI), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polystyrene, polyethylene, polypropylene, polybutadiene rubber, and polyisoprene.

[0112] The lithium-ion battery of the present invention is described in detail below through specific embodiments.

[0113] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0114] Example 1

[0115] This embodiment provides a lithium ion battery, and the preparation method thereof comprises the following steps:

[0116] 1) Preparation of positive electrode

[0117] The positive electrode active material O2 phase lithium cobalt oxide LiCoO2, binder polyvinylidene fluoride (PVDF 500), and conductive carbon black (Super P) were mixed in a mass ratio of 95:2:3, added to N-methylpyrrolidone (NMP) solvent, and continuously stirred under the action of a stirrer to form a uniform and flowing positive electrode slurry; then, the positive electrode slurry was coated on an aluminum foil with a thickness of 10 μm, sent to a vacuum oven at 120 ° C for 6 hours, and then rolled and cut to obtain a compacted density of 4.15 g / cm 3 The positive electrode;

[0118] Among them, O2 phase lithium cobalt oxide has a hexagonal R3m space group, and in the X-ray diffraction spectrum of the positive electrode active material including O2 phase lithium cobalt oxide, there is a (103) peak corresponding to the 103 crystal plane, and the half-peak width of the (103) peak is 0.135. Figure 1 This is the X-ray diffraction pattern of the positive electrode active material.

[0119] 2) Negative electrode preparation

[0120] The negative electrode active materials graphite, conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber were mixed in a mass ratio of 97.5:1:0.5:1, deionized water was added, and the mixture was continuously stirred in a stirrer to form a uniform and flowing negative electrode slurry; the negative electrode slurry was evenly coated on the surface of a copper foil with a thickness of 10 μm, and dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a compacted density of 1.67 g / cm 3 A negative electrode sheet, wherein the thickness of the negative electrode active material layer is 50 μm.

[0121] 3) Isolation film

[0122] The surface of a polyethylene substrate with a thickness of 8 μm is coated with a 2 μm polyvinylidene fluoride layer on one side and a 1 μm mixed layer of polyvinylidene fluoride and aluminum oxide (the mass ratio of polyvinylidene fluoride to aluminum oxide is 5:95) on the other side. A 2 μm polyvinylidene fluoride layer is then coated on the surface of the mixed layer to contact the negative and positive electrodes, respectively.

[0123] 4) Preparation of electrolyte

[0124] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), ethylene carbonate, propylene carbonate and propyl propionate solvents are mixed in a mass ratio of 20:10:70 to form a uniform mixed solvent; then, 14.3wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte is slowly added thereto, and after dissolution, 30% of the fluorine-containing compound fluoroethylene carbonate based on the total mass of the electrolyte is added; after stirring evenly, the electrolyte is obtained after passing the moisture and free acid tests.

[0125] 5) Preparation of lithium-ion batteries

[0126] After the positive electrode sheet, separator and negative electrode sheet prepared above are stacked (wherein the side of the separator coated with the polyvinylidene fluoride layer faces the positive electrode sheet, and the side coated with the mixed layer of polyvinylidene fluoride and aluminum oxide and the polyvinylidene fluoride layer faces the negative electrode sheet), they are wound to obtain a bare battery cell, and then the bare battery cell is placed in an aluminum-plastic film package; the prepared electrolyte is injected into the dried bare battery cell, and after vacuum packaging and standing at room temperature, high-temperature formation is performed. The formation mechanism is: at 80°C, charged at 0.2C to an upper limit voltage of 4.45V, to obtain the lithium-ion battery of this embodiment.

[0127] The preparation methods of the lithium-ion batteries in Examples 2 to 9 are basically the same as those in Example 1, except that, in step 4), the type of the fluorine-containing compound is adjusted. The specific adjustment is shown in Table 1.

[0128] The preparation methods of the lithium-ion batteries in Examples 10 and 11 are substantially the same as those in Example 1, except that, in step 4), the mass percentage of the fluorine-containing compound in the electrolyte is adjusted, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly. The specific adjustments are shown in Table 1.

[0129] The preparation method of the lithium-ion battery in Example 12 to Example 14 is basically the same as that in Example 1, except that in step 1), the type of O2 phase lithium cobalt oxide is adjusted. The specific adjustment is shown in Table 1.

[0130] The preparation method of the lithium-ion battery in Example 15 is basically the same as that in Example 1, except that, in step 1), the positive electrode active material includes both O2 phase lithium cobalt oxide and O3 phase lithium cobalt oxide LiCoO2. Specifically, the positive electrode active material can be obtained by uniformly mixing the O2 phase lithium cobalt oxide and the O3 phase lithium cobalt oxide; wherein the mass proportion C of the O2 phase lithium cobalt oxide is 25%.

[0131] The preparation method of the lithium-ion battery in Example 16 to Example 19 is basically the same as that in Example 15, except that in step 1), the mass content of O2 phase lithium cobalt oxide in the positive electrode active material is adjusted. The specific adjustment is shown in Table 1.

[0132] The preparation method of the lithium-ion battery in Example 20 to Example 24 is basically the same as that in Example 15, except that in step 4), a nitrile additive is added to the electrolyte and the mass content of the mixed solvent in the electrolyte is reduced accordingly. The specific adjustments are shown in Table 2.

[0133] The preparation method of the lithium ion battery in Example 25 and Example 26 is basically the same as that in Example 20, except that in step 4), the mass percentage of the nitrile additive in the electrolyte is adjusted, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly. The specific adjustments are shown in Table 2.

[0134] The preparation method of the lithium-ion battery in Example 27 to Example 29 is basically the same as that in Example 20, except that in step 4), 1,3-propane sultone is added to the electrolyte. The specific adjustments are shown in Table 2.

[0135] The preparation method of the lithium-ion battery in Example 30 and Example 31 is basically the same as that in Example 1, except that in step 2), the thickness of the negative electrode active layer is adjusted. The specific adjustment is shown in Table 2.

[0136] The preparation method of the lithium-ion battery in Example 32 to Example 34 is basically the same as that in Example 1, except that in step 2), the negative electrode active material also includes silicon-carbon material, and its specific mass content in the negative electrode active material is shown in Table 2.

[0137] The preparation method of the lithium-ion battery in Example 35 is basically the same as that in Example 1, except that in steps 1) and 2), the positive electrode current collector and the negative electrode current collector are replaced with a composite current collector. Specifically, the positive electrode current collector includes a stacked Cu layer (1 μm), a PET layer (3 μm) and a Cu layer (1 μm); the negative electrode current collector includes a stacked Al layer (1.2 μm), a PI layer (3 μm) and an Al layer (1.2 μm).

[0138] The preparation method of the lithium-ion battery in Example 36 is basically the same as that in Example 1, except that in step 4), the mass percentage content F of the fluorine-containing compound in the electrolyte is adjusted to 48%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0139] The preparation method of the lithium-ion battery in Example 37 is basically the same as that in Example 1, except that in step 1), the half-peak width of the O2 phase lithium cobalt oxide is 0.212.

[0140] The preparation method of the lithium-ion battery in Example 38 is basically the same as that in Example 15, except that in step 1), the mass content of O2 phase lithium cobalt oxide in the positive electrode active material is 62%.

[0141] The preparation method of the lithium-ion battery in Example 39 is basically the same as that in Example 20, except that in step 4), the content of the nitrile additive in the electrolyte is adjusted to 8%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0142] The preparation method of the lithium ion battery in Example 40 is substantially the same as that in Example 20, except that, in step 1), the mass content of O2 phase lithium cobalt oxide in the positive electrode active material is 40%;

[0143] In step 4), the content of the nitrile additive in the electrolyte is adjusted to 2%, the content of the fluorine-containing compound is adjusted to 10%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0144] The preparation method of the lithium-ion battery in Example 41 is basically the same as that in Example 14, except that the mass content of the Na element in the positive electrode active material layer is adjusted to 6500 ppm.

[0145] The preparation method of the lithium-ion battery in Example 42 is basically the same as that in Example 1, except that the mass content of the Co element in the O2 phase lithium cobalt oxide is adjusted so that the mass content of the Co element in the negative electrode sheet after formation is 56.62 ppm.

[0146] The preparation method of the lithium-ion battery in Example 43 is basically the same as that in Example 1, except that the content of Co in the O2 phase lithium cobalt oxide is adjusted so that the mass content of the Co element in the electrolyte after formation is 27.24 ppm.

[0147] The preparation method of the lithium ion battery in Example 44 is basically the same as that in Example 27, except that in step 4), the mass content of 1,3-propane sultone in the electrolyte is adjusted to 5%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0148] The preparation method of the lithium-ion battery in Example 45 is basically the same as that in Example 1, except that in step 2), the thickness of the negative electrode active layer is adjusted to 75 μm.

[0149] The preparation method of the lithium-ion battery in Example 46 is basically the same as that in Example 33, except that the mass content of the silicon-carbon material in the negative electrode active material is adjusted to 30%.

[0150] Comparative Example 1

[0151] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 4), the electrolyte does not include fluorine-containing compounds, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0152] Comparative Example 2

[0153] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 4), the mass content of the fluorine-containing compound in the electrolyte is adjusted to 53%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0154] Comparative Example 3

[0155] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 4), the mass content of the fluorine-containing compound in the electrolyte is adjusted to 62%, and the mass content of the mixed solvent in the electrolyte is adjusted accordingly.

[0156] The basic parameters are shown in Tables 1 and 2.

[0157] Table 1

[0158]

[0159]

[0160]

[0161] Table 2

[0162]

[0163]

[0164] Test Case

[0165] 1. The mass content of the Na element in the positive electrode sheet in the above embodiment and the comparative example is tested, and the lithium ion battery after formation is disassembled to obtain an electrolyte and a negative electrode sheet, and the mass content of the Co element in the electrolyte and the negative electrode sheet is tested respectively, comprising the following steps:

[0166] The disassembled negative electrode sheet is dissolved into a solution by acid, and then the electrolyte and the negative electrode solution are diluted in equal amounts and detected by inductively coupled plasma mass spectrometry (ICP-MS) to obtain the mass content of the Co element in the negative electrode sheet after formation and the mass content of the Co element in the electrolyte after formation.

[0167] The test results are shown in Table 3.

[0168] Table 3

[0169]

[0170]

[0171]

[0172] 2. The lithium-ion batteries of the above embodiments and comparative examples were tested for the following performances:

[0173] 1) Cycle performance

[0174] The lithium-ion battery prepared as above was placed in an ambient temperature of 25±2°C, and charged to 4.45V at a constant current density of 1.2C, with a cut-off current of 0.025C. After the battery was fully charged, it was left for 5 minutes, and then discharged at a constant current density of 0.5C, with a cut-off voltage of 3.0V, and the discharge capacity was recorded as the initial capacity Q1; according to the above-mentioned charge and discharge mechanism, it was cycled for 700 times, and the last discharge capacity Q2 of the battery was recorded, then the capacity retention rate (%) = Q2 / Q1×100%, and the calculation results are shown in Table 4.

[0175] 2) Charge and discharge efficiency

[0176] The lithium-ion battery prepared as above was placed in an ambient temperature of 25±2°C, and charged at a constant current of 0.1C to an upper cut-off voltage of 4.45V, a cut-off current of 0.025C, and the charging capacity Q3 was recorded; after being left for 10 minutes, the battery was discharged at a constant current of 0.1C to a discharge termination voltage of 3V, and the discharge capacity Q4 was recorded. The charge and discharge efficiency (%) = Q4 / Q3×100%, and the calculation results are shown in Table 4.

[0177] 3) Overcharge performance

[0178] The lithium ion battery prepared as above was placed in an ambient temperature of 25°C, charged to 4.45V at a constant current of 0.1C, and then kept at a constant voltage for 7 hours. After the charge, the battery was left to stand for 2 hours to observe the battery status. The battery was considered to have passed the test when there was no leakage, fire or explosion. Five samples were tested for each embodiment and comparative example, and the number of samples that passed was recorded. The results are shown in Table 4.

[0179] 4) Furnace temperature test

[0180] The prepared lithium ion battery was charged at a constant current of 1.2C to 4.45V at an ambient temperature of 25°C, with a cut-off current of 0.025V, at which time the battery was fully charged. It was then placed horizontally on a tray in an oven, and the equipment was set to heat the temperature to 130°C at a heating rate of 5±2°C / min, and placed in this environment for 60min; after the end, it was allowed to stand for 2h and the battery status was observed; when the battery did not leak, catch fire or explode, it was recorded as passing the test. Five samples were tested for each embodiment and comparative example, and the number of passing samples was recorded. The recorded results are shown in Table 4.

[0181] 5) Mechanical impact test

[0182] The lithium ion battery prepared as above was charged to 4.45V at a constant current of 1.2C at an ambient temperature of 25°C, with a cut-off current of 0.025V. At this time, the battery was fully charged. The fully charged battery was installed in a fixture, and the fixture was installed on the impact table. It was subjected to an equivalent impact force once in the X / Y / Z direction. The initial acceleration was set to 80g, and the peak acceleration was set to 150g (g is the acceleration of gravity); after the end, it was allowed to stand for 2h and the battery status was observed; when the battery did not leak, catch fire or explode, it was recorded as passing the test. Five samples were tested for each embodiment and comparative example, and the number of passing samples was recorded. The recorded results are shown in Table 4.

[0183] Table 4

[0184]

[0185]

[0186]

[0187] From Table 1 to Table 4, we can see that:

[0188] Compared with Comparative Examples 1 to 3, the lithium-ion batteries in Examples 1 to 46 have higher capacity retention, charge and discharge efficiency, overcharge performance and safety performance; the capacity retention rate of the lithium-ion battery in Example 27 can reach 76.74%, the charge and discharge efficiency can reach 80.15%, the overcharge performance can reach, and correspondingly, the number of furnace temperature test passes is 4P / 5T, and the number of mechanical impact test passes is 5P / 5T, which is significantly higher than that of Comparative Examples 1 to 3. It can be seen that the lithium-ion battery in the present invention has higher cycle stability, charge and discharge efficiency and safety.

[0189] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material; The positive electrode active material comprises lithium cobalt oxide in an O2 phase, and the X-ray diffraction spectrum of the positive electrode active material has a (103) peak corresponding to a 103 crystal plane, and the half-peak width of the (103) peak is Z, in units of degrees; The electrolyte includes a fluorine-containing compound, and based on the total mass of the electrolyte, the mass content of the fluorine-containing compound is F, in units of %; Among them, F and Z satisfy 90≤F / Z≤375.

2. The lithium-ion battery according to claim 1, characterized in that The O2 phase lithium cobalt oxide includes Li x Na y Co z M n O2, wherein 0.8<x<1.3, 0<y<0.04, 0.001<n<0.02, 0.98<z<0.999, and M comprises at least one of Al, Mg, Ti, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te; And / or, the fluorine-containing compound includes at least one of fluoroethylene carbonate, trifluoroethyl methyl carbonate, difluoroacetamide, fluorocarbamate, fluorotetramethylene sulfone, fluorotriethyl phosphate, 2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 2,2-difluoroethyl acetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorobenzene, fluoroacetonitrile, and fluoroadiponitrile.

3. The lithium ion battery according to claim 1 or 2, characterized in that: 10%≤F≤45%, and / or, 0.1°≤Z≤0.2°.

4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The positive electrode active material also includes lithium cobalt oxide in the O3 phase; Preferably, the chemical composition of the lithium cobalt oxide in the O3 phase is Li a Co e N f O2, wherein 0.9<a<1.1, 0.95≤e≤1, 0≤f≤0.05, and N includes at least one of Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te.

5. The lithium-ion battery according to claim 4, characterized in that: Based on the total mass of the positive electrode active material, the mass proportion C of the lithium cobalt oxide in the O2 phase satisfies: 5%≤C≤60%; preferably, 10%≤C≤40%; And / or, the electrolyte further includes a nitrile additive; preferably, the nitrile additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, trans-butene dinitrile, trans-hexene dinitrile, acrylonitrile, cinnamonitrile, cyclohex-1-enyl acetonitrile, 3,3-dimethylacrylonitrile, pentenenitrile, 1,4-dicyano-2-butene, and isophthalonitrile; more preferably, based on the total mass of the electrolyte, the mass content N of the nitrile additive satisfies: 2%≤N≤7%.

6. The lithium-ion battery according to claim 5, characterized in that: N, F and C satisfy 0.5≤(N+F) / C≤10.

7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The mass content of the Na element in the positive electrode active material layer is 100 to 5000 ppm; And / or, the mass content of Co element in the negative electrode sheet is 2 to 50 ppm; And / or, after the lithium ion battery is formed, the mass content of Co element in the electrolyte is 5 to 25 ppm.

8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The electrolyte also includes 1,3-propane sultone and / or 1,3-propylene sultone; Preferably, based on the total mass of the electrolyte, the mass content of the 1,3-propane sultone is 1 to 5%; Preferably, based on the total mass of the electrolyte, the mass content of 1,3-propene sultone is 0.3-3%.

9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; the single side thickness of the negative electrode active material layer is 35 to 72 μm; Preferably, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material; More preferably, based on the total mass of the negative electrode active material layer, the mass content of the silicon-carbon material is 3% to 25%.

10. The lithium ion battery according to claim 9, characterized in that: The positive electrode current collector and / or the negative electrode current collector comprises a first metal conductive layer, an organic polymer material layer and a second metal conductive layer which are stacked.